Sistem Monitoring Kualitas Tanaman Padi Berdasarkan Warna Daun dan pH Tanah Menggunakan Internet of Things Berbasis GPS - Gatot Santoso; Slamet Hani; Gafirudi Gafirudi (Prosiding Sains dan Teknologi, 2022)
Along with the development of technology the use of control systems has been widely used in various aspects, one of which is the measurement of rice field conditions that are still manual will be less efficient in terms of time, because the measurement must go down directly to the field. To solve the problem, a system is needed that can monitor the condition of rice fields continuously. The method used in the study can use several parameters, namely changes in humidity, pH, global positioning system (GPS) and color sensor to know the quality of rice through leaf color. Outoput data from each sensor will be sent to farmers via the internet of things with the help of blynk application. The accuracy of leaf color and soil pH measuring instruments connected to the blynk application is very good, with a pH sensor reading of 99.2%. The accuracy of the GPS module is 10 m from the location indicated in the study. Keyword: sensor, Internet of Things, GPS